Peningkatan Kompetensi Pedagogik Guru SMK Melalui Pelatihan Pembuatan E-Learning - Towip Towip; Yuyun Estriyanto; Ngatou Rohman; Suharno Suharno (DEDIKASI: Community Service Reports, 2020)
The covid-19 pandemic has changed the culture of teaching and learning activities in the schools. Learning activities are conducted online with the use of e-learning. Generally, Vocational High Schools (SMK) already have supporting facilities for the implementation of e-learning such as computer laboratories and adequate internet networks. However, most of the teachers in the schools are still not ready for the massive use of e-learning. For this reason, schools need training for teachers to optimize the use and integration of information and communication technology (ICT) in learning activities. The purpose of this community service is to provide training to teachers of SMK Muhammadiyah Delanggu to make e-learning and implement it in the learning process. This activity involved all teachers of SMK Muhammadiyah Delanggu. The stages of this training are: a) introduction to the concept of online learning (e-learning), b) workshop of creating e-learning, and c) application of e-learning into the subjects taught by each teacher. The results of this training: a) the teachers have been able to make learning packages, materials, and activities in the e-learning, b) Pedagogical competences of teachers have increased showed by a readiness to integrate ICT in the learning process, and c) The readiness of the school to optimize the application of e-learning to improve the learning process.